Distinction between rhinovirus‐induced acute asthma and asthma‐augmented influenza infection. Issue 5 (3rd April 2018) - Guibas, G. V.; Tsolia, M.; Christodoulou, I.; Stripeli, F.; Sakkou, Z.; Papadopoulos, N. G.
Summary: Background: Rhinovirus (RV) is an established trigger of asthma attacks, whereas such a link is less consistent for influenza virus (IFV). Objective: In the context of precision medicine, we hypothesized that IFV infection may cause a condition essentially different from RV, and we investigated this by evaluating clinical characteristics of RV/IFV‐positive and ‐negative children with respiratory symptoms and/or fever. Methods: One thousand two hundred and seven children, 6 months to 13 years old, hospitalized for flu‐like illness were recruited in this cross‐sectional study. Collected information included demographics, medical history, symptoms/physical findings/diagnosis at presentation and treatment. Nasal secretions were PCR‐tested for IFV/RV. Associations were evaluated with adjusted logistic regression models. Results: Rhinovirus positivity was associated with an asthma‐like presentation, including increased wheeze/effort of breathing/diagnosis of acute asthma, and decreased fever/vomiting. Conversely, IFV + children presented with less wheeze/effort of breathing/diagnosis of acute asthma, while they were more frequently febrile. In those with previous asthma history, both viruses induced wheeze; however, IFV was uniquely associated with a more generalised and severe presentation including fever, rales, intercostal muscle retractions and lymphadenopathy. These symptoms were not seen in RV + asthmatics, who had fewer systemic signs and more cough. Conclusions and Clinical relevance: In children with respiratory symptoms and/or fever, RV but not IFV is associated with wheeze and an asthma‐like presentation. In those with an asthma history, IFV causes more generalised and severe disease that may be better described as "asthma‐augmented influenza" rather than an "asthma attack." Differences in the acute conditions caused by these viruses should be considered in the design of epidemiological studies.